Effects of Turmeric Addition on the Physicochemical Characteristics and Preference Levels of Lemon-Date Infused Water - Abdillah, Fitri; Pujimulyani, Dwiyati; Tamaroh, Siti (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2024)
Infused water is a beverage prepared by soaking ingredients to allow flavor and nutrients to dissolve in water. Infused water offers an alternative way to consume water with rich in vitamins. This study aimed to examine the effect of soaking time and turmeric addition on the physicochemical characteristics, as well as preference levels of infused water made with lemon and dates. A 2-factorial Completely Randomized Design was employed, considering soaking durations of 4; 6; and 8 hours, and turmeric additions of 5; 10; and 15 g. The results showed that soaking time and turmeric addition significantlybai influenced the vitamin C content, antioxidant activity, turbidity, and color of the infused water. The best-infused water combination was obtained with an 8-hour soaking time and 5 g of turmeric addition, yielding a vitamin C content of 7.74 mg/100 g, an antioxidant activity of 8.22%RSA, pH of 3.76, and turbidity of 21.65 FTU.